Analysing the Impact of Foreign Direct Investment on Economic Growth in South Africa: The Role of Political Stability - Mthimkhulu, Nompumelelo Mpumi; David, Oladipo Olalekan; Stiglingh-Van Wyk, Abigail (International Journal of Economics and Financial Issues, 2025)
The complex relationship between foreign direct investment (FDI), political stability, and economic growth remains a critical area of study, particularly for developing economies like South Africa. This research investigates how FDI impacts economic growth in South Africa, with a special focus on the role political stability plays in moderating this effect. The study aims to contribute to the ongoing debate about the importance of political conditions for maximising the benefits of FDI. Using a dataset covering the period from 1994 to 2023, the study employs an Autoregressive Distributed Lag (ARDL) model, which allows for both short- and long-run dynamics to be captured between economic growth, FDI, political stability, labour force, and human capital growth. The ARDL approach was selected due to its flexibility in dealing with variables that are integrated at different levels, ensuring robust and reliable estimates. The results indicate that while human capital stock has a positive impact on long-term economic growth, both labour force expansion and human capital growth exhibit negative effects in the short and long run, suggesting inefficiencies in labour productivity and rapid educational growth. Contrary to earlier research that suggested stable political contexts inevitably promote the favourable effects of FDI, the interplay between FDI and political stability unexpectedly demonstrates a negative influence on growth. This study adds new insights by highlighting that the sectoral allocation of FDI and the quality of governance may be more important than political stability alone in driving growth. These findings fill a gap in the literature by addressing the specific case of South Africa and underscore the need for targeted FDI policies and labour market reforms to ensure that both FDI and labour contribute more effectively to economic development. The practical implications suggest that policymakers should focus on improving labour productivity and strategically managing FDI to promote sustainable growth.